2006
DOI: 10.5688/aj700118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Education in Jordan, Saudi Arabia, and Kuwait

Abstract: The practice of pharmacy, as well as pharmacy education, varies significantly throughout the world. In Jordan, Kuwait, and Saudi Arabia, the profession of pharmacy appears to be on the ascendance. This is demonstrated by an increase in the number of pharmacy schools and the number of pharmacy graduates from pharmacy programs. One of the reasons pharmacy is on the ascendance in these countries is government commitment to fund and support competitive, well-run pharmacy programs. In this report we describe pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 0 publications
2
104
0
2
Order By: Relevance
“…In Jordan; society has not readily considered the community pharmacist as a health care professional. 4 Negative views and lack of privacy during the dispensing process have been reported by Saudi people. 5 Infrequent interaction between pharmacists and pharmacyattendees has been reported in Kuwait.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Jordan; society has not readily considered the community pharmacist as a health care professional. 4 Negative views and lack of privacy during the dispensing process have been reported by Saudi people. 5 Infrequent interaction between pharmacists and pharmacyattendees has been reported in Kuwait.…”
Section: Introductionmentioning
confidence: 99%
“…3 Studies on public views towards community pharmacists have been conducted in Middle East countries. 4,5 Yet, information from Iraq is not available; and addressing that provides base line data before introducing new strategies for public health. 3 A review of studies conducted in several Arabic countries showed relatively poor attitudes towards the role of the community pharmacist.…”
Section: Introductionmentioning
confidence: 99%
“…26 The duration and content of pharmacy education differs among countries. 27,28 Although the basic pharmaceutical courses are similar, the pharmaceutical care concept has variations with regard to the practice applied in the region/country. 29e35 Recently, it has been demonstrated that simulation centers for health professional schools may offer a novel method of teaching and evaluating health care processes at the microlevel.…”
Section: Pharmacy Educationmentioning
confidence: 99%
“…The sixth year is the experiential year, during which students spend 14 weeks in community and hospital pharmacies, followed by 5 consecutive 6-weeks rotations in various medical specialties. 1 In addition to the BSc and PharmD programs available, several pharmacy schools offer postgraduate degrees such as Masters of Science (MSc) in pharmaceutical sciences, clinical pharmacy, and drug design, and a Doctor of Philosophy (PhD) in pharmaceutical sciences. 2 Despite these structured programs, pharmacy graduates with a BSc or PharmD degree are considered unprepared to practice in most pharmacy-related settings.…”
Section: Introductionmentioning
confidence: 99%